Improving the stuck-at fault coverage of functional test sequences by using limited-scan operations. - Pomeranz, I. (IEEE Transactions on VLSI systems)
Functional test sequences were shown to detect unique defects in VLSI circuits. This is thought to be due to the fact that they are applied at-speed. However, functional test sequences do not achieve complete stuck-at fault coverage. Therefore, scan-based stuck-at tests, as well as other types of tests, are typically also applied. This increases the amount of test resources required for test application. We describe a procedure for inserting (limited) scan operations into a functional sequence in order to improve its stuck-at fault coverage, thus reducing or eliminating the need for separate scan-based stuck-at tests. Between scan operations, the functional test sequence can still be applied at-speed; however, a higher stuck-at fault coverage is achieved.